KOMPETENSI GURU SEKOLAH PENGGERAK DALAM MENYUSUN MODUL AJAR KURIKULUM MERDEKA - Heni Mulyani; Magfirotun Nur Insani (Jurnal Lingkar Mutu Pendidikan, 2023)
Teachers are at the forefront of determining the success or failure of implementing a curriculum. The capacity of a teacher in compiling teaching modules is very important in the implementation of The Merdeka Curriculum. The teaching module is alearning plan hat becomes the tachers’s reference in the implementation of the learning process. This study aims to obtain an overview of the competence of teachers in comiling teaching modules in “school mover”. The method used in collecting data is Descriptif Qualitatif method, namely interviews and observations, also equipped with a questionnaire given to 69 teachers at the elementary, junior high and high school levels. The results of this study indicate the teacher's ability to understand the Merdeka Curriculum teaching modules criteria, namely 56.52% understand, 27.54% understand enough and 15.94% do not understand The ability in compiling the core components of the teaching module namely Learning Objectives. The teacher's ability to distinguish the core components and complementary components in the teaching module,namely 62.32% are at the level of understanding, 30.43% are quite understanding and 7.25% are not understanding. Learning Activities and Assessments are as follows. The ability of teachers to set learning objectives 56.52% at the capable level, 21,74% quite capable and at the less able level 21,74% In compiling learning activities 65% at the able level, 28% quite capable and at the underprivileged 7% While the ability to compose an assessment 39.13% at the capable level, 42.03% quite capable 18.84% less capable.